2008
DOI: 10.1159/000127337
|View full text |Cite
|
Sign up to set email alerts
|

Lymphocyte Subsets in Renal Transplant Recipients with de novo Genitourinary Malignancies

Abstract: Introduction: The incidence of genitourinary tumors (GUT) in renal transplant recipients (RTR) is higher than in the general population. We previously reported that CD4 lymphocytopenia is associated with a high incidence of skin cancer in RTR. Here, we investigate whether persistent CD4 T cell lymphopenia is associated with GUT occurrence. Patients and Methods: A total of 433 patients were included in this study. All patients underwent annually systematic lymphocyte subset (CD3, CD4, CD8, CD19) determination b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2009
2009
2013
2013

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 73 publications
(49 reference statements)
0
2
0
1
Order By: Relevance
“…We previously demonstrated that persistent CD4 + T cell lymphopenia is correlated with enhanced risks of cancers −including skin cancers (Ducloux et al, 1998a), monoclonal gammapathies (Ducloux et al, 1999), lymphomas as well as other non skin cancers such as colon or lung cancers (Ducloux et al, 2002a)−, of opportunistic infections (Ducloux et al, 1998b) and atherosclerotic events (Ducloux et al, 2003) in renal transplant recipients. In contrast, CD4 + T cell lymphopenia seems not to be associated with de novo genitourinary malignancies (Guichard et al, 2008). Moreover, we recently associated CD4 + T cell lymphopenia and renal transplant recipient mortality .…”
Section: Cd4mentioning
confidence: 77%
“…We previously demonstrated that persistent CD4 + T cell lymphopenia is correlated with enhanced risks of cancers −including skin cancers (Ducloux et al, 1998a), monoclonal gammapathies (Ducloux et al, 1999), lymphomas as well as other non skin cancers such as colon or lung cancers (Ducloux et al, 2002a)−, of opportunistic infections (Ducloux et al, 1998b) and atherosclerotic events (Ducloux et al, 2003) in renal transplant recipients. In contrast, CD4 + T cell lymphopenia seems not to be associated with de novo genitourinary malignancies (Guichard et al, 2008). Moreover, we recently associated CD4 + T cell lymphopenia and renal transplant recipient mortality .…”
Section: Cd4mentioning
confidence: 77%
“…This persistent CD4 + T cell depletion is also correlated with the increased incidence of opportunistic infections [38] and of atherosclerotic events [39]. On the opposite, CD4 + T cell lymphopenia seems not to be associated with de novo genitourinary malignancies [40]. Recently, we associated prolonged CD4 + T cell lymphopenia and renal transplant recipient mortality [41].…”
Section: Persistent Cd4 + T Cell Lymphopenia a Biomarker For Immunosmentioning
confidence: 99%
“…Problematisch ist sicherlich die Definition dieser Risikogruppe. Hier gibt es erste Ansätze mithilfe der flowzytometrischen Bestimmung von Lymphozytensubpopulationen [28]. Untersucht wird hier die Bedeutung der CD4-T-Lymphozyten, die insbesondere beim Auftreten von Tumoren des Urogenitaltraktes vermindert sind.…”
Section: Transplantierte Neoplasienunclassified